The Effect of the Carbon to the S11 Measurement on the Pyramidal Microwave Absorbers - Imran , Mohd Ibrahim; Mohd Nor , Husain; Azizah , Shaaban; Sian Meng, Se (2011)
The purpose of this work is to determine the absorption effect by using carbon as absorbing material. It will be used in anechoic chamber in order to avoid reflections that occur on the wall of the chamber. From polystyrene, the absorbers are cut into pyramidal shaped. The pyramidal shaped is chosen because it could meet the specified industrial standards which can work well at microwave frequency. To verify the performance of the absorber, a measurement is conducted to determine the absorption rate in frequency range 1 to 10 GHz. The absorber also compared to commercial absorber. The results shows carbon is a good material to absorb the microwave energy. The absorber that has been developed is a low cost with reliable performance.